Bahasa Rupa Komik Black Metal Istiqomah pada Pos Instagram (Tokoh Varokah dan Setan) - Nasruddin, Merlina Fatimah (Visualita Jurnal Online Desain Komunikasi Visual, 2020)
Achmad Deptian Djenuari Rizky is an Indonesian illustrator who carries emotional black metal themes, horror, and grim spiritual values ​​of western black metal or heavy metal in the style of his illustrations. In Black Metal Istiqomah's post Instagram upload series, Deptian raised Islamic spiritual values, propaganda values, and local values ​​that were paired with a visual theme of the expression of the flow of black metal music. Elements of black metal expression that are aggressive and tend to be rebellious with subtle Islamic values ​​and polite Islamic characteristics are two contrasting elements. The purpose of this study is to discuss the expressions and stories of each object using the Tabrani’s visual language method. The discussion on how to use speech and expressions so that it becomes visual language that can be told based on visible speech, is used to reveal which position is the element of emphasis between Islamic values ​​and thematic black metal in the visual style it carries. In Deptian's Black Metal Istiqomah Instagram post, a version of the Varokah character story with a devil character, Satan's wage is described as having a dominant portion in the frame and has a reference to the demonic illustration in European satanism.